Dança de encantados: uma trama de remendos: o terecô na cidade de Teresina-PI - Alencar, Robert Rodrigues de (2023)
The proposed work aims to contribute to the literature about the Terecô Dance in the city of Teresina-PI, starting from the experiences embodied in the Terreiro Tenda Nossa Senhora Santana located in the south zone of the capital of the state of Piauí, seeking to understand the processes of religious intertwining that formed diasporic afro-religious identities in Teresina. The research aims to answer whether there is a correct form or method for dancing Terecô, and how the body is organized in the action. Here what I call plots will be presented, which when put together undertake to analize and presnete the elements that weave the universo of Terecô patches, understandin the body not only as a human physical structure but as all those thta present momories, narratives and singularities. To pursue these objectives, this study was carried out with a qualitative approach, supported by principles based on Oral History. I used as methodological resources, bibliographical research that presents a historiographical narrative about Terecô and the processes of intertwining with other religiosities found in Teresina, as well as literature that dialogues the relationship between Body and Dance with Terecô, I will also use recorded interviews, records photographs and on-site experience.